A Semantic Theory for Value-Passing Processes Based on the Late Approach - Ingólfsdóttir, Anna (BRICS Report Series, 2003)
A general class of languages for value-passing calculi based on the late semantic approach is defined and a concrete instantiation of the general syntax is given. This is a modification of the standard CCS according to the late approach. Three kinds of semantics are given for this language. First a Plotkin style operational semantics by means of an applicative labelled transition system is introduced. This is a modification of the standard labelled transition system that caters for value-passing according to the late approach. As an abstraction, late bisimulation preorder is given. Then a general class of denotational models for the late semantics is defined. A denotational model for the concrete language is given as an instantiation of the general class. Two equationally based proof systems are defined. The first one, which is value-finitary, i. e. only reasons about a finite number of values at each time, is shown to be sound and complete with respect to this model. The second proof system, a value-infinitary one, is shown to be sound with respect to the model, whereas the completeness is proven later. The operational and the denotational semantics are compared and it is shown that the bisimulation preorder is finer than the preorder induced by the denotational model. We also show that in general the omega-bisimulation preorder is strictly included in the model induced preorder. Finally a value-finitary version of the bisimulation preorder is defined and the full abstractness of the denotational model with respect to it is shown. It is also shown that for CCS_L the omega -bisimulation preorder coincides with the preorder induced by the model. From this we can conclude that if we allow for parameterized recursion in our language, we may express processes which coincide in any algebraic domain but are distinguished by the omega-bisimulation. This shows that if we extend CCS_L in this way we obtain a strictly more expressive language.